Improved analysis of volatile halogenated hydrocarbons in water by purge-and-trap with gas chromatography and mass spectrometric detection - ZOCCOLILLO, Lelio; INSOGNA, SUSANNA; Luca Amendola; Claudia Cafaro (Journal of Chromatography A, 2005)
An analytical system composed of a purge-and-trap injection system coupled to gas chromatography with mass spectrometric detection (PTI-GC-MS) specific for the analysis of volatile chlorinated hydrocarbons (VCHCs) (chloroform; 1, 1, 1-trichloroethane; tetrachloromethane; 1, 1,2-trichloroethylene; tetrachloroethylene) and trihalomethanes (THMs) (chloroform; bromodichloromethane; dibromochloromethane; bromoform) in water was optimised. Samples were purged and trapped in a cold trap (-100 degrees C) fed with liquid nitrogen (cryo-concentration). In order to make this method suitable also for only slightly contaminated waters, some modifications were made to PTI sample introduction, in order to avoid any air intake into the system. PTI, GC and MS conditions were optimised for halogenated compound analysis and limits of detection (LOD) were evaluated. The proposed method allows analysis of samples whose concentrations range from mu g/L to ng/L. It is, therefore, applicable to drinking waters, in analyses required by law, and to slightly contaminated aqueous matrices, such as those found in remote areas, in environmental monitoring. Moreover, by changing cold trap temperature, even sparkling mineral waters can be analysed, thus avoiding CO2 interference during the cryo-concentration phase. Our method has been successfully used on real samples: tap Water, mineral water and Antarctic snow. (C) 2005 Elsevier B.V. All rights reserved.